2016
DOI: 10.1371/journal.pone.0151474
|View full text |Cite
|
Sign up to set email alerts
|

Are MUPs a Toxic Waste Disposal System?

Abstract: Male house mice produce large quantities of major urinary proteins (MUPs), which function to bind and transport volatile pheromones, though they may also function as scavengers that bind and excrete toxic compounds (‘toxic waste hypothesis’). In this study, we demonstrate the presence of an industrial chemical, 2,4-di-tert-butylphenol (DTBP), in the urine of wild-derived house mice (Mus musculus musculus). Addition of guanidine hydrochloride to male and female urine resulted in an increased release of DTBP. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…This hypothesis or as we call it the ‘toxic waste hypothesis’27 has later been suggested by another laboratory72 with the first experimental evidence provided in a recent paper42. They demonstrated that mice loaded with an industrial chemical, 2,4-di-tert-butylphenol (DTBP) use MUPs for a consequent detoxification42. Here we suggest that the nasal and olfactory lipocalins (including MUPs) transport potential toxic waste and various degradation products from chemical signals to the oral cavity, and further to the digestive tract where they are decomposed.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This hypothesis or as we call it the ‘toxic waste hypothesis’27 has later been suggested by another laboratory72 with the first experimental evidence provided in a recent paper42. They demonstrated that mice loaded with an industrial chemical, 2,4-di-tert-butylphenol (DTBP) use MUPs for a consequent detoxification42. Here we suggest that the nasal and olfactory lipocalins (including MUPs) transport potential toxic waste and various degradation products from chemical signals to the oral cavity, and further to the digestive tract where they are decomposed.…”
Section: Discussionmentioning
confidence: 79%
“…We have already suggested that evolution of chemical communication and of the system of detoxification might have been driven by similar selective forces because both systems use the same pool of lipocalin transporters2731. This hypothesis or as we call it the ‘toxic waste hypothesis’27 has later been suggested by another laboratory72 with the first experimental evidence provided in a recent paper42. They demonstrated that mice loaded with an industrial chemical, 2,4-di-tert-butylphenol (DTBP) use MUPs for a consequent detoxification42.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, many species do not have multiple copies of Mup genes and thus MUP products-a major component of chemical signaling and olfaction in mice and rats-but express functional OBPs. This has been shown in many mammals (Singer and Macrides, 1990;Stopkova et al, 2010;Hagemeyer et al, 2011;Nagnan-Le Meillour et al, 2014) and it is our hope that potentially diverse functionsi.e., including the detoxification roles (Stopková et al, 2009;Kwak et al, 2011Kwak et al, , 2016)-of these proteins will be further resolved.…”
Section: Discussionmentioning
confidence: 99%
“…The "toxic waste hypothesis" states that various lipocalins are involved in removing toxic waste from the body (Stopková et al, 2009;Kwak et al, 2011) and that some of the compounds might have been constituting a signal under selection (Stopková et al, 2009). The toxic waste disposal role has been experimentally demonstrated in a recent paper (Kwak et al, 2016) where mice loaded with an industrial chemical, 2,4-di-tertbutylphenol (DTBP) used MUPs for a consequent detoxification (Kwak et al, 2016). To conclude, lipocalins are ubiquitous proteins with diverse functions and multiple sites of their expression.…”
mentioning
confidence: 99%
“…The low individual variation of Mup genes and linked microsatellites suggest that these genes are evolving under purifying selection26, perhaps through a selective sweep in this large region40, and the high homology of different Mup loci may be generated by concerted evolution (gene conversion)4142. It is unclear why selection favours low individual variation and high homology of MUP loci, and studies are needed to investigate possible effects on individual survival43, as well as reproductive success (through chemical communication).…”
Section: Discussionmentioning
confidence: 99%